Dynamic road lane management study: A Smart City application. (May 2016) - Wang, Chen; David, Bertrand; Chalon, René; Yin, Chuantao
Highlights: ICT-based dynamic road lane management system. System architecture: main components of the overall system. Internet of Things and Location-Based Services as main principles. Simulator for capacity studies and driving situation usability testing. On-board embedded user interface design and testing and Mock-up technology validation. Abstract: Our Smart City contribution is transportation-oriented in that it proposes a dynamic road lane management system in order to share appropriately the space devoted to traffic. After a historical view of a series of solutions from physical to ICT supported, we present our proposal extensively supported by up-to-date ICT. Following a main presentation, we describe the system architecture and its working conditions. Then, we present the proposed simulator designed to study operating and driver's conditions with respect to the new traffic signs proposed. We also describe a Mock-up technology validation and give preliminary information on in-the-field deployment.